The role of desaturases in the biosynthesis of marking pheromones in bumblebee males - Buček, Aleš; Vogel, Heiko; Matoušková, Petra; Prchalová, Darina; Záček, Petr; Vrkoslav, Vladimír; Šebesta, Petr; Svatoš, Aleš; Jahn, Ullrich; Valterová, Irena; Pichová, Iva (Insect biochemistry and molecular biology, 2013)
Bumblebee males (Hymenoptera) produce species-specific labial gland secretions called marking pheromones (MPs). MPs generally consist of terpenoids and fatty-acid-derived aliphatic compounds with various chain lengths predominantly containing one or no double bonds. The unsaturated fatty-acid-derived MP components were hypothesized to be produced by fatty acid desaturases (FADs) that exhibit diverse substrate specificities. To address this hypothesis, we isolated and functionally characterized FADs from three bumblebee species: Bombus lucorum, Bombus terrestris, and Bombus lapidarius. By employing RNA sequencing of the male labial glands and fat bodies of B. lucorum and B. terrestris, we identified five paralogous FAD-like sequences but only two FAD lineages were abundant and differentially expressed in the labial glands. We found that abundant FAD lineages were also expressed in the labial gland and fat body of Bombus lapidarius. Functional characterization of FADs in a yeast expression system confirmed that Δ4-FADs exhibited a unique Δ4-desaturase activity exclusively on 14-carbon fatty acyls and Δ9-FADs displayed Δ9-desaturase activity on 14- to 18-carbon fatty acyls. These results indicate that Δ9-FADs are involved in the biosynthesis of major unsaturated components of MPs in B. lucorum and B. lapidarius despite the diverse MP composition of these bumblebee species. The contribution of lipases, acyltransferases, esterases, and fatty acid reductases to production of the species-specific MP composition is also discussed in light of the transcriptomic data obtained in this study.
Keywords: real-time quantitative PCR; feromony; Sequence Analysis, DNA; fatty acid; DMDS; ORF; labial gland; dimethyl disulfide; stearyl-CoA-desaturasa; fat body; open reading frame; Fatty Acid Desaturases; RPKM; qPCR; Me; ethyl ester; gas chromatography – mass spectrometry; desaturasy mastných kyselin; mužské pohlaví; Pheromones; Hymenoptera; trans-membrane; GC/MS; FAEE; zvířata; hmyzí proteiny; fylogeneze; FAR; Fatty acid desaturase; methylester; MP; Et; Bumblebee; Stearoyl-CoA Desaturase; FA; sekvenční analýza DNA; včely; RNA-seq; FAD; Functional expression; reads per kilobase of exon model per million mapped reads; marking pheromone; fatty acid reductase; LG; Bees; Insect Proteins; Phylogeny; Pheromone; fatty acid ethyl ester; FB; fatty acid desaturase; Male; TM; Animals